Pengaruh Store Atmosphere, Viral Marketing dan Physical Evidence terhadap Minat Beli Konsumen pada Café Om Kopi di Kota Malang (Studi Pada Mahasiswa Manajaemen UNISMA Angkatan 2019) - Inrah Wati Juwita; Nurhajati Nurhajati; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this research is to find out and explain the influence of store atmosphere, viral marketing and physical evidence on consumer buying interest at the Om Kopi café in Malang City. This research uses a quantitative approach with explanatory research. Sampling in this study was 105 respondents who were UNISMA students class of 2019, the method of data collection used a purposive sampling technique which had certain criteria. The analytical method used is multiple regression analysis with the help of the IBM SPSS 26 program. The results of this study indicate that store atmosphere, viral marketing and physical evidence simultaneously have a significant effect on consumer buying interest. The store atmosphere variable has a significant effect on consumer buying interest, viral marketing has no significant effect on consumer buying interest, and physical evidence has a significant effect on consumer buying interest. Keywords: Store Atmosphere, Viral Marketing, Physical Evidence, Buying Interest